Pemahaman Nilai-nilai Bela Negara Generasi Muda Dalam Mnghadapi Informasi Di Era Digital - Yulnelly, Yulnelly; Setiyawati, Marina Ery (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
UPN “Veteran” Jakarta is one of 3 (three) State Universities (PTN) which initially had the status of a Private Universities (PTS) until 2014 changed its status to PTN with the characteristics of State Defense. Defending the State is the effort of ev ery citizen in maintaining the integrity of his country where this situation is realized, among others, by an attitude of love for the homeland and being willing to sacrifice. Along with advances in the field of information technology, it is very easy and fast to get information from various social media, so a wise attitude is needed in sorting information. Based on this, a research was conducted with the title Understanding the Values of State Defense of the Young Generation in Facing Information in the Digital Age. This study aims to find out and get an overview of the younger generation regarding Bela values in the digital era. The method used to obtain data and information by using a questionnaire as an instrument of data collection from a predetermined sample that can represent the population. The research approach is quantitative research with descriptive research methods, namely all information or data presented in the form of numbers and data analysis is carried out to obtain conclusions. The results obtained this study are that there is still an inappropriate understanding of the concept of Defending the State and there are still young people who are not wise in using social media in the digital era